Jesus' family tree - Cox, Ana ([Australia : BBC Active, 2004)
These filmchronicle the practical, and moral, backing of a vast extended family from his parents, Joseph and Mary, to his grandfather, Joachim, his cousin, John the Baptist, and his brothers, Simon, Jude, Joseph and James
Executive producer, Jean-Claude Bragard ; editor, James Mareon
Narrated by Tom Hodgkins
Keywords: Jesus Christ -- Family; Jesus Christ; Christianity -- Origin